Pengaruh Konsentrasi Campuran Maizena dan Glukomanan dengan Lama Pengeringan terhadap Karakteristik Komposit Bioplastik - Siallagan, Rio Rambo; Harjosuwono, Bambang Admadi; Suhendra, Lutfi (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2022)
This study aims to determine the effect of the concentration of a mixture of cornstarch and glucomannan with drying time and the interaction of the two on the characteristics of bioplastics and to determine the concentration of the mixture of cornstarch and glucomannan with the best drying time. This study used a factorial randomized experimental group design. The first factor is the concentration of the cornstarch-glucomannan mixture from 4 levels, namely 4%, 5%, 6%, and 7% (w/w). The second factor is the stirring time which consists of 4 levels, namely 5,6,7, and 8 hours . The results showed that the concentration of the cornstarch-glucomannan mixture with drying time had a very significant effect on tensile strength, elongation at break and thickness development/swelling, but had no significant effect on biodegradation. The interaction between treatments had a significant effect on the tensile strength and the rate of water vapor transmission. concentration of cornstarch-glucomannan mixture of 6% and drying time of 6 hours produced the best characteristics of bioplastic composites with a tensile strength value of 22.82 MPa, elongation at break of 11.01%, elasticity value of 353.50 MPa, swelling of 87.98%, the value of the water vapor transmission rate of 1.42 g/m 2 .hour and the biodegradation time of 7 days. The results of functional group analysis showed that the cornstarch glucomannan bioplastic composite contained hydroxyl (OH), carbonyl (C=O), carboxyl (CO) and -(CHhydrocarbon groups 2 )n